A assinatura digital em contratos de câmbio: estudo de caso em um banco brasileiro - Abud, Jordan Ribeiro (2011)
The Digital Signature on Foreign Exchange Contracts has appeared in 2004, and it is a process that emerges as an alternative to the traditional process of manual signature on contracts. This work intends, through a quantitative analysis of a Brazilian bank data base, search for behavior patterns that may exist in digitally signed foreign exchange operations, according with the size of companies and its segmentation in the Bank. The foreign exchange market concept will be analyzed, and also its structure and pattern in Brazil. The Digital Signature process will be deeply analyzed, showing concepts necessary for its correct work model, like cryptography, hash functions, digital certificates and public key infrastructure. As contributions of the study will be present the importance of the Digital Signature process at the present time, the growth and the relevance of small and medium companies using Digital Signature and the differences between the market segmentation of the companies.